Formulated fuel and preparation process thereof - ZHANG XIAOQUN (2011)
The invention belongs to the technical field of energy saving, environment friendliness and resource reutilization, and in particular relates to a formulated fuel and a preparation process thereof. The formulated fuel comprises the following components in part by weight: 70 to 99 parts of coal serving as a main material, and 1 to 30 parts of at least one of mineral material, carbide slag and industrial waste serving as an additive, wherein the mineral material comprises gallium oxide (GaO), silicon dioxide (SiO2), aluminum oxide (Al2O3) and iron oxide (Fe2O3). All the components are mixed to prepare the formulated fuel. In actual industrial application, the formulated fuel can be cooperatively used in coal thermal power plants, large industrial boilers, industrial furnaces, city heat supply and the like; and the formulated fuel is directly transported to industrial sites, which contributes to environment friendliness, improves the efficiency and truly realizes industrial application.